Cognitive and Mood Profiles Among Patients With Stiff Person Syndrome Spectrum Disorders - Chan, Carol K.; Pimentel Maldonado, Daniela A.; Wang, Yujie; Obando, Danielle; Hughes, Abbey J.; Newsome, Scott D. (Frontiers in Neurology, 2022)
An emerging body of evidence suggests that changes in cognitive and emotional function are common aspects of stiff person spectrum disorders (SPSD). We sought to examine the pattern of cognitive impairment and psychiatric symptoms in SPSD. Methods A retrospective review of medical records was conducted for patients seen at the Johns Hopkins Stiff Person Syndrome (SPS) center from 1997 to January 1st, 2020. Individuals who had received formal cognitive testing as part of routine clinical care for patient-reported cognitive changes were included. Demographics, prevalence of cognitive impairment, psychoactive medication use, and clinically significant psychiatric symptoms were described. Results Out of 205 patients screened, 20 completed cognitive testing (75% female, mean age 47.4 years). The most common domains of impairment were verbal learning and recall memory (n = 14, 70%), verbal fluency (n = 10, 50%), processing speed (n = 8, 40%), and attention (n = 8, 40%). 9/11 patients assessed for depression reported clinically significant symptoms, and 4/9 patients assessed for anxiety reported clinically significant symptoms. Conclusions Screening for cognitive impairment in SPSD should utilize testing that assesses verbal learning and recall, phonemic verbal fluency, attention, and processing speed. Moreover, it is important to evaluate for co-existing depression and anxiety symptoms, as these are common in SPSD.